(untitled) (Annals of Medical Research, 2021)
Aim: The objective of this study is to evaluate the effectiveness of ursodeoxycholic acid (UDCA) for the treatment of symptomatic pregnant women with gall bladder stones and/or sludge. Material and Methods: Gynecology and obstetrics clinic patients who were symptomatic with gallbladder stones and/or microlithiasis were included in the study. Group 1 consisted of cases with conservative treatment and group 2 consisted of cases with UDCA treatment. After treatment, the groups were compared for symptomatic and radiological relief and hospitalization. Results: For group 2, the mean treatment time with UDCA was 7.6 weeks. After treatment, a full cure was achieved in 28% of cases and symptomatic relief was achieved in 36% of cases. In group one; there was response to treatment in only 12% of cases. In the UDCA group, none of the patients needed hospitalization; however, in the conservative treatment group, five cases needed hospitalization. Conclusion: UDCA is effective for the treatment of symptomatic gall bladder disease in pregnancy. It both relieves symptoms and decreases the need for hospitalization.